The Effect of HRM Practices on Employees' Work Engagement and the Mediating and Moderating Role of Positive Psychological Capital - Aybas, Meryem; Acar, Ahmet Cevat (International Review of Management and Marketing, 2017)
This study proposes and investigates a model of psychological capital as a mediator and moderator in HR practices-employee work engagement relationship. Although there have been a lot of researches on the relationship between HR practices and individual and organizational outcomes, how occur this relationship is still unclear. In order to advance our knowledge about this relationship, there is need to investigate possible mediating and moderating variables that effective on it. To test developed model, we collected data from 590 white-collor employees who are working in private companies from different sectors in Turkey. As a result of this study the effects of motivation and skill enhancing HR practices on work engagement are significantly partial mediated by psychological capital but not moderated. On the other hand the effects of opportunity enhancing HR practices and working conditions on work engagement are significantly partial mediated and moderated by psychological capital at the same time. Keywords: HRM Practices, Work engagement, Positive Psychological Capital JEL Classifications: M12, M50, M54